Biofilm Implication in Oral Diseases of Dogs and Cats - Csilla Zambori; Emil Tîrziu; Ileana Nichita; Ciceronis Cumpanasoiu; Radu Valentin Gros; Monica Seres; Bianca Mladin; Daniela Mot (Scientific Papers Animal Science and Biotechnologies, 2023)
The importance of biofilm in disease processes in humans and animals is now widely recognized. In animal species, the risk of infection is probably greater than the risk in humans. This is due to the difference in animal housing and living environments – animals naturally live in environments with a large and much more diverse microbial community. Most oral bacteria live symbiotically in biofilm. This symbiotic association gives the bacteria different communal properties than individual planktonic bacteria. Bacteria that form biofilm live and develop in communities which are an important property for dental plaque formation that leads to dental calculus formation, periodontal diseases, dental caries and systemic diseases. The objective of this study is to reveal the role of dental plaque (oral biofilm) in pathogenesis of dental calculus, periodontal disease and dental caries in dogs and cats.